2022
DOI: 10.1039/d2cc01164f
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of nanopore transport performance by polymer functionalization

Abstract: Inspired by the design and performance of biological pores, polymer functionalization of nanopores has emerged as an evolving field to advance transport performance within the last few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 220 publications
(318 reference statements)
0
23
0
Order By: Relevance
“…the increasing number of reported visible light induced polymerizations. [1][2][3] Polymer functionalized nanopores, for example, allow for specific control of molecular transport which is relevant in separation, energy conversion, sensing, or release. 2,[4][5][6][7][8][9][10] Especially, gating of molecular transport using stimuli-responsive polymers in nanopores has been demonstrated for all possible stimuli from pH, ion interaction to redox or even magnetic gating.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…the increasing number of reported visible light induced polymerizations. [1][2][3] Polymer functionalized nanopores, for example, allow for specific control of molecular transport which is relevant in separation, energy conversion, sensing, or release. 2,[4][5][6][7][8][9][10] Especially, gating of molecular transport using stimuli-responsive polymers in nanopores has been demonstrated for all possible stimuli from pH, ion interaction to redox or even magnetic gating.…”
Section: Introductionmentioning
confidence: 99%
“…Such asymmetric design of porous materials has been shown to result in Janus materials for side selective separation or increased transport performance. 3,12 For example, theoretical studies from Huang and Szleifer demonstrated the relevance of controlled and local nanopore functionalization, as well as polymer sequence design of nanopores allowing transport direction. 13,14 An experimental implementation of local polymer functionalization including polymer sequence design has to be based on controlled (living) polymerizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, high ionic rectification factors above 1000 for asymmetric designed nanopores have been theoretically demonstrated 10 by implementing two orthogonal gates at both entrances of a nanopore. 10 Although controlled polymer functionalization of nanopores significantly advanced within the last years, 1,2,11 experimental examples on local polymer placement and sequence control remain a challenge and need local polymer placement and controlled polymerization. Polymerization control in nanopores is most often achieved by surface-initiated atom transfer radical polymerization (SI-ATRP), SI-RAFT, or iniferter-initiated polymerizations.…”
mentioning
confidence: 99%
“…Despite the numerous examples of gated nanopore transport, transport direction as well as selectivity is still a challenge in technological pores. 1,2 To date, directional transport has been experimentally demonstrated in Janus materials. [3][4][5][6] With respect to individual nanopores transport direction and ion rectication has been shown for asymmetrically shaped nanoscale pores and channels.…”
mentioning
confidence: 99%